2018
DOI: 10.1038/s41598-018-29772-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of whisker follicles in methamphetamine self-administered rats

Abstract: Methamphetamine (MA) is a highly addictive psychostimulant that disturbs the central nervous system; therefore, diagnosis of MA addiction is important in clinical and forensic toxicology. In this study, a MA self-administration rat model was used to illustrate the gene expression profiling of the rewarding effect caused by MA. RNA-sequencing was performed to examine changes in gene expression in rat whisker follicles collected before self-administration, after MA self-administration, and after withdrawal sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…However, in this context, it is noteworthy that Arc is required for postsynaptic trafficking and processing of Appand amyloid β formation, which appear to be relevant to AD pathogenesis [ 31 ]. In whisker follicles, the App gene has been identified as a potential marker gene, which is in agreement with our previous data suggesting that App is an addiction-related gene in the whisker follicle in MA self-administered rats [ 9 ]. Although much remains to be studied, we cannot ignore the possibility that MA-induced genetic changes disturbing homeostatic synaptic plasticity in the brain are somehow reflected in whisker follicles, thereby linking the functions between striatal tissues and whisker follicle tissues.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, in this context, it is noteworthy that Arc is required for postsynaptic trafficking and processing of Appand amyloid β formation, which appear to be relevant to AD pathogenesis [ 31 ]. In whisker follicles, the App gene has been identified as a potential marker gene, which is in agreement with our previous data suggesting that App is an addiction-related gene in the whisker follicle in MA self-administered rats [ 9 ]. Although much remains to be studied, we cannot ignore the possibility that MA-induced genetic changes disturbing homeostatic synaptic plasticity in the brain are somehow reflected in whisker follicles, thereby linking the functions between striatal tissues and whisker follicle tissues.…”
Section: Discussionsupporting
confidence: 91%
“…After co-examining the gene expression in hair follicles and post-mortem brain tissue samples from patients with autism, they suggested that hair follicles may serve as an alternative apparatus reflecting the state of the central nervous system [ 8 ]. Consistently with this finding, our previous data have revealed that alterations of gene expression patterns in the whisker follicles of MA self-administered rats may serve as useful indicators of MA rewards [ 9 ]. However, to date, large-scale evaluation and comparison of the molecular changes have not been conducted between hair follicles and the striatum.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The radiological response evaluation was performed by two board-certified radiologists according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST). 25 Target lesions were defined as those with the largest diameter of 1 cm or more and non-target lesions as those with largest diameter of less than 1 cm. 25 To evaluate treatment response, two lesions per organ and five lesions in total were maximally selected.…”
Section: Radiological Evaluationmentioning
confidence: 99%